LITERASI KEUANGAN (FINANCIAL LITERACY) MAHASISWA INDEKOS CALON PENDIDIK EKONOMI FKIP UNIVERSITAS JEMBER - Titin K Kartini; Udik Mashudi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The level of financial literacy among students in Indonesia is still low. This is in accordance with the results of the OJK survey in 2016, which was only 28.3%. This figure explains that most students in Indonesia still do not understand financial concepts. Students who are known as intellectuals should be able to manage their personal finances independently, well, carefully and responsibly. Managing expenses is actually not a difficult thing, if the person concerned can distinguish things that must take precedence/priority with only fulfilling desires. The aim of the research was to analyze descriptively the level of financial literacy in boarding students as prospective economic educators at FKIP University of Jember. In taking the sample, the researcher used purposive sampling method. The sample used in this study was 50 prospective students of economics educators at FKIP University of Jember who were boarding children or overseas children who still depended on remittances/ pocket money from their parents every month. Data collection in this study used questionnaires which were distributed directly to respondents and some were distributed indirectly using Googleform. The results of the study showed that the level of financial literacy of students as prospective economic educators at FKIP University of Jember was good with an average score of 82.67% and was in the high category.Keywords: financial literacy, boarding students, prospective economic educators